Effect of Lipid Content on Anaerobic Digestion Process and Microbial Community: Review Study - Alhraishawi, Ali; Aslan, Sukru (European Scientific Journal, ESJ, 2022)
The indiscriminate release of significant amounts of food waste, fat oil and grease, and sewage sludge (SS) into the environment causes severe contamination in many nations. There are numerous potential treatment methods to cope with the organic wastes, but anaerobic digestion is currently widely accepted to handle different kinds of biological waste. One of the pillars supporting anaerobic digester biogas production increase in treatment plants is the use of fats in the wastewaters. However, it has been claimed that high-fat wastes, particularly mono-digestion in the anaerobic reactor, inhibits acetoclastic and methanotrophic bacteria, delays the formation of gas even more, and overtaxes the system. This paper examines the research on the impact of lipids on biogas enhancement, reactor inhibition, impact on the microbial communities, and co-digestion with lipids in the anaerobic digestion process.